Pengaruh Religiusitas dan Love of Money Terhadap Kepatuhan Wajib Pajak UMKM di Kecamatan Batujajar - Saputrie, Viona Ayu; Feriyanto, Oon (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the influence of religiosity and love of money on tax compliance of Micro, Small, and Medium Enterprises (SMEs) in Batujajar District. Tax compliance plays an important role in supporting state revenues, but there are still many MSMEs who have not fully fulfilled their tax obligations. Religiosity is believed to increase tax compliance through moral and ethical values, while love of money tends to decrease tax compliance because it focuses on personal financial gain. This study applies a quantitative approach with a survey method using a questionnaire distributed to 94 SMEs in Batujajar District. The data obtained were analyzed using multiple linear regression to test the relationship between the independent variables (religiosity and love of money) and the dependent variable (tax compliance). The results of the study indicate that religiosity has a positive and significant impact on tax compliance, which means that the higher a person's level of religiosity, the greater their willingness to fulfill tax obligations. Conversely, the tendency to love money has a negative and significant effect, indicating that the higher a person's level of love of money, the lower their compliance in paying taxes. Therefore, increasing religiosity can be a driving factor for tax compliance for SMEs, while love of money has the potential to be an obstacle in fulfilling tax obligations.